2015
DOI: 10.1039/c4mt00228h
|View full text |Cite|
|
Sign up to set email alerts
|

X-Ray fluorescence imaging and other analyses identify selenium and GPX1 as important in female reproductive function

Abstract: Studies of selenium (Se) status indicate that Se is necessary for fertility but how precisely is not known. We aimed to show that Se was important in bovine female reproductive function. The elemental distribution in the bovine ovary (n = 45 sections) was identified by X-ray fluorescence (XRF) imaging. Se was consistently localized to the granulosa cell layer of large (>10 mm) healthy follicles. Inductively Coupled Plasma - Mass Spectrometry revealed tenfold higher Se in the bovine follicle wall compared to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 49 publications
6
61
0
3
Order By: Relevance
“…Dietary deficiency of essential trace elements such as Se has been shown to impair the mammalian reproductive physiology [9,10,28]. In a well-known previous study on 112 patients undergoing in vitro fertilization (IVF) procedures, Paszkowski and colleagues [29] reported that detectable traces of Se were observed in human follicular fluid, and it was shown that subjects with idiopathic infertility had significantly lower Se levels compared to those who were suffering from known causes of infertility.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary deficiency of essential trace elements such as Se has been shown to impair the mammalian reproductive physiology [9,10,28]. In a well-known previous study on 112 patients undergoing in vitro fertilization (IVF) procedures, Paszkowski and colleagues [29] reported that detectable traces of Se were observed in human follicular fluid, and it was shown that subjects with idiopathic infertility had significantly lower Se levels compared to those who were suffering from known causes of infertility.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite past evidence of Se implication in female fertility and reproduction, there are more studies focusing on the role of Se in male reproduction [10]. There is still a comparative dearth of adequately powered mechanistic and functional studies elucidating the wider implications of Se and selenoproteins in female fertility and reproduction [9,28]. Available evidence highlights that studies focusing on role of Se as an essential trace element in female reproduction are mainly focused on human pregnancy [30] and related complications such as pre-eclampsia [31], miscarriage and preterm birth [9,32], intrauterine growth restriction [33], small-for-gestational age newborns [34], pregnancy-induced hypertension [35], and pregnancy-related autoimmune thyroid disease [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceko et al 386 aimed to show that Se is important in the bovine female reproductive function. This state-of-the-art paper included as well as nomenclature, denitions, as examples of calibration strategies with analytical calibration procedures.…”
Section: Biologicalmentioning
confidence: 99%
“…However, the oocyte development within the follicular structure involves uninterrupted two‐way dialogs between the oocyte and cumulus complex, as well as the other somatic cells in the follicles, such as the granulosa and theca cells (Wigglesworth et al., 2013). The granulosa cells are important components of the follicular environment for the achievement of oocyte capability, ovulation, and fertilization as they regulate the expression of luteinizing hormone receptor (LHR), production of estradiol and progesterone, Inhibin A and B secretion, and production of several transcripts vital proteins (Ceko et al., 2014; Hatzirodos et al., 2014). The bone morphogenetic protein 15 and growth differentiation factor 9, belong to the TGF‐β superfamily, act on the granulosa cells to regulate oocyte growth and differentiation.…”
Section: Introductionmentioning
confidence: 99%